A Ni-doped Co3O4 nanosheet active material and its preparation method and its application in NO sensors
By preparing Ni-doped Co3O4 nanosheet active materials, the problems of insufficient sensitivity, selectivity and stability of existing NO sensors are solved, realizing rapid and high-sensitivity detection of NO at room temperature, reducing humidity interference, and making it suitable for NO sensors.
Patent Information
- Application Number
- CN202610220094.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-24
- Publication Date
- 2026-06-30
AI Technical Summary
Existing NO sensors have shortcomings in terms of sensitivity, selectivity, response speed and stability. In particular, they are difficult to achieve high sensitivity and fast response under room temperature conditions, and are easily affected by humidity.
A method for preparing Ni-doped Co3O4 nanosheet active materials was adopted. A metal-organic precursor with a MOF-like structure was formed by reacting 2-methylimidazole with a mixed solution of cobalt salt and nickel salt. After calcination, sheet-like Ni-doped Co3O4 materials were formed, which were used to construct membrane electrode components and NO sensors.
It achieves rapid and highly sensitive detection of NO at room temperature, improves response speed and stability, reduces humidity interference, and is suitable for use as a NO sensor.
Smart Images

Figure CN122301274A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of nitric oxide detection equipment technology, specifically to a Ni-doped Co3O4 nanosheet active material and its preparation method, as well as its application in NO sensors. Background Technology
[0002] Nitric oxide (NO) is a significant air pollutant, primarily originating from fossil fuel combustion and industrial emissions. It is a crucial precursor in the formation of acid rain and photochemical smog. In the atmosphere, NO readily transforms into NO2 through photochemical reactions; both are NO compounds. x Components. Compared to NO2, which is relatively stable and easy to detect, NO is highly reactive, easily oxidized, and difficult to capture stably at room temperature. This leads to significant uncertainties in its sampling, transmission, and detection processes, making accurate monitoring of NO a critical challenge. x Technical challenges in monitoring systems. Abnormal NO concentrations not only damage the ecological environment but may also reduce the blood's oxygen-carrying capacity by binding to hemoglobin in the human body, thereby triggering or aggravating respiratory and cardiovascular diseases. Based on these environmental and health risks, environmental authorities in various countries monitor atmospheric NO levels. x Strict limits have been set for NO emission concentrations to continuously strengthen NO emission control. x With PM 2.5 The coordinated control of NO and the promotion of high-density, real-time air pollution monitoring networks in key industrial zones are needed. However, mainstream NO... x While detection equipment, such as chemiluminescence analyzers, offers high detection accuracy, they generally suffer from complex system structures, large size, high cost, and difficulties in achieving distributed and mobile monitoring, particularly in the rapid response and interference-resistant detection of NO. Furthermore, NO is an important endogenous signaling molecule in the human body, and its levels are closely related to the occurrence and development of various diseases. Exhaled NO concentration has been widely used as an important biomarker for airway verification and has significant application value in the auxiliary diagnosis of diseases such as asthma. This detection method requires advantages such as being non-invasive, convenient, and having a rapid response, while also placing higher demands on the sensor's detection limit, selectivity, and response speed. There is an urgent need for NO sensors with ppb-level sensitivity and good stability.
[0003] Currently, methods for NO detection include colorimetric analysis, gas chromatography-mass spectrometry, chemiluminescence, and electrochemical methods. However, these methods often suffer from limitations in practical applications, such as complex operating procedures, high equipment costs, and difficulty in miniaturization. In contrast, gas sensors have attracted widespread attention due to their simple structure, ease of integration, and suitability for real-time online detection. Among these, while metal oxide semiconductor gas sensors have made some progress in sensitivity and stability, they still suffer from problems such as high operating temperatures, insufficient selectivity, long response times, and significant susceptibility to humidity interference, limiting their application in high-precision NO detection scenarios. In recent years, electrochemical gas sensors based on metal oxides have attracted widespread attention due to their advantages of high selectivity, fast response speed, low power consumption, and easy miniaturization. Among existing technologies, Chinese patent CN107082455A discloses a method for preparing nickel-doped cobalt tetroxide nanoparticles. This method involves adding nickel salt, cobalt salt, and urea to an ethanol-water solution, reacting at 120-180°C for 10-12 hours, and then calcining in air at 400°C for 2 hours to obtain nickel-doped cobalt tetroxide nanoflowers with a flower-like structure formed by numerous nanorods surrounding a central core. Urea is used as a precipitant, and OH- is released through the slow decomposition of urea. - Inducing metal hydroxide precipitation makes nucleation and growth processes difficult to control precisely. The dense flower-like structure prolongs the gas adsorption and TOF pathway, resulting in longer response and recovery times. Furthermore, the presence of grain boundaries and structural stress between the rods makes the nanoflower-like structure prone to collapse or breakage of the links between nanorods when applied to NO sensors, leading to decreased sensitivity and short lifespan.
[0004] To address the shortcomings of existing NO sensors in terms of sensitivity, selectivity, response speed, and stability, a novel nickel-doped cobalt tetroxide structure is urgently needed to solve these problems. Summary of the Invention
[0005] (a) Technical problems to be solved
[0006] To address the shortcomings of existing technologies, this invention provides a Ni-doped Co3O4 nanosheet active material and its preparation method, as well as its application in NO sensors, thus solving the problems mentioned in the background section.
[0007] (II) Technical Solution
[0008] To achieve the above objectives, the present invention provides the following technical solution:
[0009] According to a first aspect of the present invention, a method for preparing Ni-doped Co3O4 nanosheet active materials is provided, comprising the following steps:
[0010] Step 1: Dissolve the cobalt salt and nickel salt in a mixed solvent and stir until homogeneous to obtain solution A;
[0011] Step 2: Add 2-methylimidazole to methanol and stir until homogeneous to obtain solution B;
[0012] Step 3: Slowly add solution B to solution A, carry out the first reaction at room temperature, then transfer to a reaction vessel for the second reaction, vacuum dry, and calcine to obtain Ni-doped Co3O4 nanosheet active material.
[0013] Preferably, the molar ratio of the cobalt salt, nickel salt, and 2-methylimidazole is 1:0.005~0.03:0.001~2, wherein the nickel salt and cobalt salt are both expressed in molar amounts based on their metal element content.
[0014] The mixed solvent includes methanol and water, and the mass ratio of methanol to water is 1:1 to 2.
[0015] Preferably, the nickel salt is selected from at least one of nickel nitrate hexahydrate, nickel chloride hexahydrate, and nickel acetate tetrahydrate;
[0016] The cobalt salt is selected from at least one of cobalt nitrate hexahydrate and cobalt chloride hexahydrate.
[0017] Preferably, the reaction time for the first reaction is 30 to 60 minutes.
[0018] Preferably, the temperature of the second reaction is 120~150℃ and the time is 3~5h.
[0019] Preferably, the calcination parameters are: heating to 400-450℃ at a heating rate of 2-5℃ / min and calcining for 1-3 hours.
[0020] According to a second aspect of the present invention, a Ni-doped Co3O4 nanosheet active material obtained according to the above preparation method is provided.
[0021] According to a third aspect of the present invention, a membrane electrode assembly is provided, comprising the above-described Ni-doped Co3O4 nanosheet active material.
[0022] According to a fourth aspect of the present invention, a method for preparing a membrane electrode assembly is provided, wherein 2-10 mg of the Ni-doped Co3O4 nanosheet active material is first dispersed in a mixed solution composed of isopropanol and Nafion solution, then drop-coated onto the surface of two carbon paper sheets and dried, then drop-coated onto the surface of the two carbon paper sheets with Nafion solution and dried, and finally the Nafion layer is sandwiched between the two carbon paper electrodes and hot-pressed to obtain the membrane electrode assembly.
[0023] According to a fifth aspect of the present invention, a NO sensor is provided, comprising the above-described membrane electrode assembly.
[0024] Beneficial effects
[0025] This invention provides a Ni-doped Co3O4 nanosheet active material, its preparation method, and its application in NO sensors. It offers the following advantages:
[0026] (1) The present solution provides a method for preparing Ni-doped Co3O4 nanosheet active materials, which utilizes the electron-rich N atoms in the 2-methylimidazole molecule to react with Co in the initial stage of the reaction. 2+ and Ni 2+ A stable coordination structure is formed, which induces the coordination assembly of metal ions, thereby regulating the spatial distribution of metal ions at the molecular scale and forming a MOF-like metal-organic precursor structure. After calcination, a Ni-doped Co3O4 active material with a sheet-like structure is formed.
[0027] (2) The Ni-doped Co3O4 nanosheet active material provided in this scheme has a uniform and porous sheet structure with a high specific surface area, thus exposing more surface active sites. In the construction of a fuel cell-type electrochemical NO sensor, Ni doping of Co3O4 improves... The electrical conductivity and surface reactivity of Co3O4 enable the NO sensor to achieve rapid and highly sensitive detection of low concentrations of NO at room temperature, and significantly improve response speed, stability and resistance to humidity interference. Attached Figure Description
[0028] Figure 1 Different Ni doping methods are used in this invention XRD pattern of Co3O4;
[0029] Figure 2 Different Ni doping methods are used in this invention Enlarged view of the main diffraction peak (311) in the XRD pattern of Co3O4;
[0030] Figure 3 The images shown are SEM images of Co3O4 under different Ni doping conditions according to the present invention. Among them, (a) is the SEM image of pure Co3O4 at 1 μm magnification, (b) is the SEM image of pure Co3O4 at 0.5 μm magnification, (c) is the SEM image of Co3O4-0.5%Ni at 2 μm magnification, (d) is the SEM image of Co3O4-0.5%Ni at 1 μm magnification, (e) is the SEM image of Co3O4-1%Ni at 2 μm magnification, (f) is the SEM image of Co3O4-1%Ni at 1 μm magnification, (g) is the SEM image of Co3O4-3%Ni at 2 μm magnification, and (h) is the SEM image of Co3O4-3%Ni at 1 μm magnification.
[0031] Figure 4The dynamic response curves of Co3O4 with different Ni doping to different concentrations of NO are shown.
[0032] Figure 5 This is a selective test diagram of the NO sensor based on Co3O4-1%Ni active material according to the present invention;
[0033] Figure 6 This is a statistical graph showing the response of the NO sensor based on Co3O4-1%Ni active material of this invention to NO gas at a concentration of 20ppm under different humidity conditions.
[0034] Figure 7 This is a test graph showing the long-term stability of the NO sensor based on Co3O4-1%Ni active material of this invention against NO gas at a concentration of 20 ppm. Detailed Implementation
[0035] The present invention will now be described in further detail with reference to specific embodiments and accompanying drawings. It should be understood that these embodiments are illustrative of the present application and not intended to limit its scope. Furthermore, it should be understood that after reading the contents of this application, those skilled in the art can make various alterations or modifications to the present invention, and these equivalent forms also fall within the protection scope of the appended claims.
[0036] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The use of terms as used in this specification is for the purpose of describing particular embodiments only and is not intended to be limiting of the application.
[0037] Example 1
[0038] Step 1: Weigh 4 mmol of cobalt nitrate hexahydrate and 0.02 mmol of nickel nitrate hexahydrate and dissolve them in 30 mL of a mixed solvent, which includes 20 mL of deionized water and 10 mL of methanol. Under stirring conditions, solution A is obtained.
[0039] Step 2: Weigh 8 mmol of 2-methylimidazole and dissolve it in 6 mL of methanol to obtain solution B;
[0040] Step 3: Slowly add solution B to solution A and stir continuously at room temperature for 30 min. Then transfer the mixed solution to a polytetrafluoroethylene-lined stainless steel reactor and react at 120℃ for 3 h. After the reaction is complete, allow it to cool naturally to room temperature, collect the precipitate and wash it twice with deionized water and anhydrous ethanol, then dry it in a vacuum oven. The dried sample is heated to 400℃ in a muffle furnace at a heating rate of 2℃ / min and held for 1 h to obtain Ni-doped Co3O4 nanosheet active material, denoted as Co3O4-0.5%Ni.
[0041] Example 2
[0042] Step 1: Weigh 4 mmol of cobalt nitrate hexahydrate and 0.04 mmol of nickel nitrate hexahydrate and dissolve them in 30 mL of a mixed solvent, which includes 20 mL of deionized water and 10 mL of methanol. Under stirring conditions, solution A is obtained.
[0043] Step 2: Weigh 8 mmol of 2-methylimidazole and dissolve it in 6 mL of methanol to obtain solution B;
[0044] Step 3: Slowly add solution B to solution A and stir continuously at room temperature for 30 min. Then transfer the mixed solution to a polytetrafluoroethylene-lined stainless steel reactor and react at 120℃ for 3 h. After the reaction is complete, allow it to cool naturally to room temperature, collect the precipitate and wash it twice with deionized water and anhydrous ethanol, then dry it in a vacuum oven. The dried sample is heated to 400℃ in a muffle furnace at a heating rate of 2℃ / min and held for 1 h to obtain Ni-doped Co3O4 nanosheet active material, denoted as Co3O4-1%Ni.
[0045] Example 3
[0046] Step 1: Weigh 4 mmol of cobalt nitrate hexahydrate and 0.12 mmol of nickel nitrate hexahydrate and dissolve them in 30 mL of a mixed solvent, which includes 20 mL of deionized water and 10 mL of methanol. Under stirring conditions, solution A is obtained.
[0047] Step 2: Weigh 8 mmol of 2-methylimidazole and dissolve it in 6 mL of methanol to obtain solution B;
[0048] Step 3: Slowly add solution B to solution A and stir continuously at room temperature for 30 min. Then transfer the mixed solution to a polytetrafluoroethylene-lined stainless steel reactor and react at 120℃ for 3 h. After the reaction is complete, allow it to cool naturally to room temperature, collect the precipitate and wash it twice with deionized water and anhydrous ethanol, then dry it in a vacuum oven. The dried sample is heated to 400℃ in a muffle furnace at a heating rate of 2℃ / min and held for 1 h to obtain Ni-doped Co3O4 nanosheet active material, denoted as Co3O4-3%Ni.
[0049] Comparative Example 1
[0050] Step 1: Weigh 4 mmol of cobalt nitrate hexahydrate and dissolve it in 30 mL of a mixed solvent, which includes 20 mL of deionized water and 10 mL of methanol. Under stirring conditions, solution A is obtained.
[0051] Step 2: Weigh 8 mmol of 2-methylimidazole and dissolve it in 6 mL of methanol to obtain solution B;
[0052] Step 3: Slowly add solution B to solution A and stir continuously at room temperature for 30 min. Then transfer the mixed solution to a polytetrafluoroethylene-lined stainless steel reactor and react at 120℃ for 3 h. After the reaction is complete, allow it to cool naturally to room temperature, collect the precipitate and wash it twice with deionized water and anhydrous ethanol, then dry it in a vacuum oven. The dried sample is heated to 400℃ in a muffle furnace at a heating rate of 2℃ / min and held for 1 h to obtain pure Co3O4 nanosheet active material, denoted as Pure-Co3O4.
[0053] according to Figure 1 It can be seen that all diffraction peaks of the nickel-doped Co3O4 nanosheet active material match the standard card of cubic Co3O4 (PDF#74-2120), and no impurity diffraction peaks due to Ni clusters or nickel oxides were observed, indicating that Ni doping did not introduce an independent impurity phase structure, and the cubic crystal structure of Co3O4 remained intact. Figure 2 It can be seen that, compared with undoped Co3O4, the diffraction peaks corresponding to the (311) crystal plane show a slight shift to a lower angle, indicating that Ni atoms enter the Co3O4 lattice and cause lattice expansion.
[0054] according to Figure 3 It can be seen that although Ni doping is introduced into Co3O4, the morphology of Co3O4 does not change significantly and remains a plate-like structure.
[0055] Application examples
[0056] 5 mg of the active materials prepared in Examples 1-3 and Comparative Example 1 were dispersed in a mixed solution consisting of 460 μL isopropanol and 40 μL Nafion solution. The dispersion was ultrasonically dispersed for 2 h under ice bath conditions to obtain a dispersion. The dispersion was then drop-coated onto the surface of two 15 mm × 15 mm carbon paper substrates (HCP120) and dried thoroughly in an oven. After drying, 20 μL of Nafion solution was drop-coated onto the carbon paper surface and dried for another 2 h in an oven. The treated Nafion solution was then placed between the two carbon paper electrodes and a membrane electrode assembly was prepared by hot pressing. The obtained membrane electrode assembly was sealed and fixed to the copper electrode with hot melt adhesive. At the same time, the water storage container and the battery cathode were sealed in the device, so that only the working electrode (positive electrode) was exposed to the target gas, while the counter electrode (negative electrode) was placed in a water container filled with room temperature air.
[0057] The following performance tests were conducted using NO sensors prepared with the active materials of Examples 1 to 3 and Comparative Example 1:
[0058] Gradient tests were performed on NO concentrations ranging from 50 ppm to 50 ppb, based on... Figure 4It is known that among the NO sensors prepared by the active materials in the embodiments of this application, the NO sensor prepared by the Co3O4-1%Ni active material has the highest sensitivity, generating a response current of up to 4.52μA at a concentration of 50ppm, and still maintaining a clear and distinguishable signal at a concentration as low as 50ppb.
[0059] according to Figure 5 It is evident that the NO sensor prepared based on Co3O4-1%Ni active material in this application exhibits excellent selectivity for NO.
[0060] The response of an NO sensor based on Co3O4-1%Ni active material to a 20 ppm NO gas concentration was tested under different humidity levels. Figure 6 As shown, the response value remains stable under different humidity levels.
[0061] The response of an NO sensor based on Co3O4-1%Ni active material to a 20 ppm NO gas concentration was tested over 14 days. Figure 7 As shown, the NO sensor prepared with Co3O4-1%Ni active material maintains a response value of 1.6 μA to NO gas at a concentration of 20 ppm for 14 days, exhibiting excellent long-term stability.
[0062] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a Ni-doped Co3O4 nanosheet active material, characterized by: Includes the following steps: Step 1: Dissolve the cobalt salt and nickel salt in a mixed solvent and stir until homogeneous to obtain solution A; Step 2: Add 2-methylimidazole to methanol and stir until homogeneous to obtain solution B; Step 3: Slowly add solution B to solution A, carry out the first reaction at room temperature, then transfer to a reaction vessel for the second reaction, vacuum dry, and calcine to obtain Ni-doped Co3O4 nanosheet active material.
2. The preparation method of the Ni-doped Co3O4 nanosheet active material according to claim 1, characterized in that: The molar ratio of the cobalt salt, nickel salt, and 2-methylimidazole is 1:0.005~0.03:0.001~2, wherein the nickel salt and cobalt salt are expressed in molar amounts based on their metal element content. The mixed solvent includes methanol and water, and the mass ratio of methanol to water is 1:1 to 2.
3. The preparation method of the Ni-doped Co3O4 nanosheet active material according to claim 1, characterized in that: The nickel salt is selected from at least one of nickel nitrate hexahydrate, nickel chloride hexahydrate, and nickel acetate tetrahydrate; The cobalt salt is selected from at least one of cobalt nitrate hexahydrate and cobalt chloride hexahydrate.
4. The method for preparing Ni-doped Co3O4 nanosheet active material according to claim 1, characterized in that: The first reaction takes 30 to 60 minutes.
5. The method for preparing Ni-doped Co3O4 nanosheet active material according to claim 1, characterized in that: The temperature of the second reaction is 120~150℃, and the time is 3~5h.
6. The method for preparing Ni-doped Co3O4 nanosheet active material according to claim 1, characterized in that: The calcination parameters are: heating to 400-450℃ at a heating rate of 2-5℃ / min and calcining for 1-3 hours.
7. A Ni-doped Co3O4 nanosheet active material obtained by the preparation method according to any one of claims 1 to 6.
8. A membrane electrode assembly, characterized in that: Including the Ni-doped Co3O4 nanosheet active material as described in claim 7.
9. A method for preparing the membrane electrode assembly according to claim 8, characterized in that: First, 2-10 mg of the Ni-doped Co3O4 nanosheet active material is dispersed in a mixed solution composed of isopropanol and Nafion solution, then dropped onto the surface of two carbon paper sheets and dried. Next, Nafion solution is dropped onto the surface of the two carbon paper sheets and dried. Finally, the Nafion layer is sandwiched between the two carbon paper electrodes and hot-pressed to obtain the membrane electrode assembly.
10. A NO sensor, characterized in that: Includes the membrane electrode assembly as described in claim 8 or 9.
Citation Information
Patent Citations
Nickel-doped cobaltosic oxide nanoflower and preparation method thereof
CN107082455A